The Effect of Community Language Learning and Learning Interest Towards Students’ Speaking Ability - syahyuri syahyuri (Scope : Journal of English Language Teaching, 2018)
This research is aimed to get the empirical data and to find out the effect of Community Language Learning and learning interest towards students’ speaking ability at a private college in Bekasi. The research was conducted at school of foreign languages Cipto Hadi Pranoto in Bekasi. The total sample of this research is by 60 students. The technique of collecting data of teaching method (CLL) and learning interest used questionnaires and the speaking skill was acquired from the test. The research of the instrument has tested and tried by the validity and the reliability test used the program of SPSS 17.0 (Statistics Program Social Science). The result of the study identifies There is significant effect of learning method towards students speaking ability. Keyword: Community Language Learning, Learning Interest, and Speaking Ability